2015
DOI: 10.1111/ene.12796
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairments associated with morphological changes in cortical and subcortical structures in multiple system atrophy of the cerebellar type

Abstract: Cognitive impairment in MSA-C might result from functional disruption of the corticostriatal and pontocerebellar circuit mediated by primary cortical, cerebellar or thalamic pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
2
24
1
2
Order By: Relevance
“…Recently, neuropathological studies reported an association of neuronal cytoplasmatic inclusions in neocortex or limbic regions and cognitive impairment in MSA . Additionally, imaging data also suggest that beside atrophy of subcortical regions, thinning of neocortices may contribute to cognitive impairment . In this study, MSA‐C patients showed to be more frequently impaired in a screening of executive function, possibly resulting from disruption of cerebrocerebellar circuits.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Recently, neuropathological studies reported an association of neuronal cytoplasmatic inclusions in neocortex or limbic regions and cognitive impairment in MSA . Additionally, imaging data also suggest that beside atrophy of subcortical regions, thinning of neocortices may contribute to cognitive impairment . In this study, MSA‐C patients showed to be more frequently impaired in a screening of executive function, possibly resulting from disruption of cerebrocerebellar circuits.…”
Section: Discussionmentioning
confidence: 47%
“…9,20,21 Additionally, imaging data also suggest that beside atrophy of subcortical regions, thinning of neocortices may contribute to cognitive impairment. [61][62][63] In this study, MSA-C patients showed to be more frequently impaired in a screening of executive function, possibly resulting from disruption of cerebrocerebellar circuits. This phenomenon has also been observed in other cerebellar disorders, as the cerebellum functionally modulates higher cognition.…”
Section: Discussionmentioning
confidence: 52%
“…Indeed, it is difficult to compare VBM performed with statistical parametric mapping with cortical thickness measures, because these 2 methods are based on a completely different statistical background. Cortical thickness analysis in MSA‐C showed cortical thinning in the frontal, temporal, parietal, parahippocampal, and lingual cortices . Intriguingly, cortical thinning in the left prefrontal cortex and the right parahippocampal cortex correlated with the severity of dysarthria.…”
Section: Mri Findings Of Msamentioning
confidence: 94%
“…Cortical thickness analysis in MSA-C showed cortical thinning in the frontal, temporal, parietal, parahippocampal, and lingual cortices. 58,59 Intriguingly, cortical thinning in the left prefrontal cortex and the right parahippocampal cortex correlated with the severity of dysarthria. In MSA-P, cortical thinning was reported in the frontal motor cortex and the premotor cortex.…”
Section: Automated Volumetric and Cortical Thickness Analysesmentioning
confidence: 98%
“…Parkinson disease (PD) in its early years can be well managed with symptomatic dopaminergic therapy , whilst other movement disorders are less satisfactorily treated . The development of motor complications is a significant limitation to the long term use of levodopa.…”
mentioning
confidence: 99%